Liposomal encapsulation of silver nanoparticles enhances cytotoxicity and causes induction of reactive oxygen species‐independent apoptosis. Issue 5 (27th November 2017) - Yusuf, A.; Brophy, A.; Gorey, B.; Casey, A.
Abstract: Silver nanoparticles (AgNP) are one of the most widely investigated metallic NPs due to their promising antibacterial activities. In recent years, AgNP research has shifted beyond antimicrobial use to potential applications in the medical arena. This shift coupled with the extensive commercial applications of AgNP will further increase human exposure and the subsequent risk of adverse effects that may result from repeated exposures and inefficient delivery, meaning research into improved AgNP delivery is of paramount importance. In this study, AgNP were encapsulated in a natural biosurfactant, dipalmitoylphosphatidylcholine, in an attempt to enhance the intracellular delivery and simultaneously mediate the associated cytotoxicity of the AgNP. It was noted that because of the encapsulation, liposomal AgNP (Lipo‐AgNP) at 0.625 μg ml –1 induced significant cell death in THP1 cell lines a notably lower dose than that of the uncoated AgNP induced cytotoxicity. The induced cytotoxicity was shown to result in an increased level of DNA fragmentation resulting in a cell cycle interruption at the S phase. It was shown that the predominate form of cell death upon exposure to both uncoated AgNP and Lipo‐AgNP was apoptosis. However, a reactive oxygen species‐independent activation of the executioner caspases 3/7 occurred when exposed to the Lipo‐AgNP. These findings showed that encapsulation of AgNP enhance AgNP cytotoxicity and mediates a reactive oxygen species‐independent induction of apoptosis. Abstract : A method of encapsulating silver nanoparticles (AgNP) in liposomes (Lipo‐AgNP) is described to improve AgNP delivery and enhance its cytotoxicity. Treatment of THP1 cells at low dose of Lipo‐AgNP induced a ROS‐independent apoptosis due to DNA fragmentation and resulted in the induction of caspase 3/7. The findings indicate that Lipo‐AgNP can mediate AgNP cytotoxicity at significantly lower concentrations than standard AgNP.